Optimizing Atom Probe Analysis with Synchronous Laser Pulsing and Voltage Pulsing. (8th February 2017) - Zhao, Lu; Normand, Antoine; Houard, Jonathan; Blum, Ivan; Delaroche, Fabien; Latry, Olivier; Ravelo, Blaise; Vurpillot, Francois
Abstract: Atom probe has been developed for investigating materials at the atomic scale and in three dimensions by using either high-voltage (HV) pulses or laser pulses to trigger the field evaporation of surface atoms. In this paper, we propose an atom probe setup with pulsed evaporation achieved by simultaneous application of both methods. This provides a simple way to improve mass resolution without degrading the intrinsic spatial resolution of the instrument. The basic principle of this setup is the combination of both modes, but with a precise control of the delay (at a femtosecond timescale) between voltage and laser pulses. A home-made voltage pulse generator and an air-to-vacuum transmission system are discussed. The shape of the HV pulse presented at the sample apex is experimentally measured. Optimizing the delay between the voltage and the laser pulse improves the mass spectrum quality.